Russian Arctic Seas Navigational conditions and accidents - Marchenko, Nataly (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Important sources of information about safe shipping in the harsh sailing conditions in the Arctic are the detailed experiences of the ice pilots who have worked in those seas. To this end and in the context of planning the PetroArctic project, this valuable reference gathers accounts of seagoing activities in the Russian Arctic Seas that resulted in accidents and makes them available in this bilingual (Russian-English) volume. In particular, it describes the physical environment and navigational issues in the Kara, Laptev, East Siberian and Chukchi seas. Fully half of the book comprises nearly 100 detailed accident reports of incidents induced by heavy ice conditions, from 1900 to the present. These accidents are classified by type and cause, e.g. shipwrecks, forced drift (ice jet as special case), overwintering, and various types of vessel damage. Most accounts include details such as distinguishing features of the event, behavior of the crew, photos, and information-rich maps, which reveal the ice conditions, date, location, and vessels involved (for each of the four seas). The book will be useful to scientists, engineers, industrial planners and a wide audience interested in the Arctic Seas.